Green Experiential Marketing, Experiential Value, Relationship Quality, and Customer Loyalty in Environmental Leisure Farm - Lee, Tzai-Chiao; Peng, Michael Yao-Ping (Frontiers in Environmental Science, 2021)
Environmental/green marketing has emerged as one of the dominant paradigms of marketing in recent years. However, aspects such as internationalization, the development of artificial intelligence, and stress from growing global competitive forces have brought about changes in the way leisure farms approach experiential marketing with a significant environmental focus. In this context, the concept of relationship quality offers an opportunity for environmental leisure farms to understand how green experiential marketing impacts consumers’ perceived value and the ongoing interaction relationship. This study adopts a comprehensive perspective that includes green experiential marketing and relationship marketing that leisure farms use in order to enhance customer loyalty, and analyzes the effect of a series of elements inherent to customer psychic or personal needs. 754 valid copies of questionnaire were adopted in total. To verify the proposed model empirically, a survey of customers of environmental leisure farms in Taiwan was conducted. Structural equation modeling is conducted to examine the research hypotheses. The findings show that, overall, green experiential marketing has positive direct effects on experiential value, and experiential value has positive direct effects on trust, commitment, and satisfaction. At the same time, trust and satisfaction have positive effects on attitudinal and behavioral loyalty. In addition, attitudinal loyalty has a positive influence on behavioral loyalty.